Formulasi Strategi Ukm Jilbab Azky Collection Untuk Meningkatkann Daya Saing Di Masa Pandemi Covid-19 - Suaibatul Aslamiyah (Jurnal Manajerial, 2021)
Background - The corona virus (Covid-19) has rocked the world, WHO even declared this a pandemic, so that various policies have also been carried out by the Indonesian government to reduce the spread of the virus. However, the business world is the most affected, especially SMEs as the tip of the economy in Indonesia. Therefore, SMEs need to create a business strategy that can continue to maintain their business in the midst of a pandemic situation that is still ongoing today. Purpose - to identify internal and external conditions and formulate business strategies to improve competitiveness in the small business of the Azky Collection hijab in Melirang Wetan Village, Bungah District, Gresik Regency during the Covid-19 pandemic which is still ongoing until October 2020. Design / Methodology / Approach - This study uses a case study approach with an explanative qualitative research method. Data analysis using Expert Choice V11 software. Results and Discussion - The results showed that the analysis of the internali and externali environmenti at the Azky Collection was above average (stabel). The right strategy formulation used by Azky Collection in dealing with the Covid-19 pandemic through matrix analysis of IFE, EFE, SWOT, IE, CPM, Grand Strategy and QSPM which can increase its competitiveness is product development. Conclusion - The right strategy formulation used by Azky Collection in facing the challenges of environmental change due to the Covid-19 pandemic is product development. Research implications - This study provides a contribution to the application of strategic management related to the determination (formulation) of strategy in SMEs which are the driving force of the largest economic sector. Research limitations - The study was conducted by conducting interviews and questionnaires given via telephone and WhatsApp because they were still in a pandemic situation.